Modifiers of microbial hydrolases among new types of biscytrate germanates - Gudzenko, O.V.; Borzova, N.V.; Varbanets, L.D. (Problems of Environmental Biotechnology, 2023)
The modifiers of microbial hydrolases among new types of biscytrate germanates are considered.